Genética, citogenética, estructura floral y técnicas de hibridación de la yuca - Hershey, Clair H.; Amaya, A. (International Center for Tropical Agriculture, 1979)
A summary is made of the information available on cassava genetics, cytogenetics, flowering habits, flower structure, hybridization techniques, seed storage and germination. (CIAT)